Pengembangan Kepemimpinan Gereja Masehi Injili di Halmahera melalui Pemaknaan Filosofis Kepemimpinan Gembala - Ricardo Freedom Nanuru (Sekolah Tinggi Teologi Pelita Bangsa, Jakarta, 2020)
This study aims to find the ideal concept of leadership in church circles and make it relevant to the church process at the Evangelical Christian Church in Halmahera (GMIH). The method used is research or literature review by exploring leadership management concepts, both general in society and specifically in the church. This study found that the success or failure of a leader will indeed be seen from the results of his work. The process influences these results from the beginning of becoming a leader, the lead management process, and its evaluation, both process evaluation and work results. Leadership in the Church is the same way. One thing that needs to be instilled early in church leadership is that the leader-pastor is not God. They are only tools in God's hands because they are also not free from various weaknesses. The church does not adhere to a